Morphometric description of sandflies belong to genus Sergentomyia (Sergentomyia) (Diptera; Psychodidae; Phlebotominae) in Sri Lanka; evidence for the presence of Sergentomyia (Sergentomyia) pondicherriensis and Sergentomyia (Sergentomyia) dentata in the country - Gajapathy, K.; Surendran, S.N. (Academic Journals Inc, 2011)
Leishmaniasis, mainly a zoonotic disease vectored by sand flies, emerges as major public health concern in Sri Lanka. The role of the old world sandfly genus Sergentomyia in the disease transmission is emphasized in recent findings. Seven species belong to the subgenus Sergentomyia of this genus have been reported globally. Only one (Sergentomyia (Sergentomyia) punjabiensis) has been recorded so far from Sri Lanka. Three species viz. Se. (Ser.) punjabiensis, Se. (Ser.) pondicherriensis and Se. (Ser.) dentata were identified in a collection from three Cutaneous Leishmaniasis (CL) endemic localities in Sri Lanka. This is the first record of the presence of Se. (Ser.) pondicherriensis and Se. (Ser) dentate from the country. The detail morphology of both sexes are described along with the comparison with the existing literatures from the oriental region.
Keywords: Leishmaniasis; Sandflies; Sergentomyia; Sri Lanka; Zoonotic disease